Literasi Digital Untuk Melindungi Masyarakat Dari Kejahatan Siber - Gita Eka Sila; Cevi Mochamad Taufik (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
The digital transformation process uncovers evil. Migration from a manual pattern to an online-based system is only a condition that forces people to enter this service system. Without preparation and complete information, suddenly people are brought into a completely different atmosphere from the period they have experienced so far. Forced compulsion finally colored the journey to this new era coded 0 and 1. Various communication events, especially with regard to digital crime cases, one of which occurred by taking advantage of public ignorance. If this new era is considered a necessity, total preparation is needed. Not on the issue of infrastructure, but also mental spiritual and knowledge of the community. Responding to this problem, this research was conducted with the aim of knowing cyber crime in an atmosphere of a digitally illiterate society. Using a qualitative descriptive method, observed data sources from online media are analyzed to find clear relationships that cause the emergence of cybercrime. The results of the research show that people's lack of understanding of digital systems allows many victims to fall and fall into the traps set up by criminals. Therefore digital literacy activities must be carried out massively so that knowledge about digitalization does not trap victims. Digital literacy activities must be promoted as much as possible to touch all levels of society. This activity can be initiated by the government, private bodies, or community organizations.